2015
DOI: 10.1007/s10965-015-0783-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferric chloride as an efficient and reusable catalyst for methanolysis of poly(lactic acid) waste

Abstract: Ferric chloride (FeCl 3 ) was used to catalyze the methanolysis of poly(lactic acid) (PLA) to recover methyl lactate. The effects of experimental parameters such as reaction temperature, reaction time, amount of FeCl 3 and dosage of methanol on results were studied in detail. The results showed that under the optimized reaction conditions of n(methanol):n(PLA)=5:1, n(FeCl 3 ):n(PLA)=0.01:1, 130°C and 4.0 h, the conversion of PLA reached 96.0 % and the yield of methyl lactate was up to 87.2 %. FeCl 3 could be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
0
33
1
Order By: Relevance
“…Compared to other waste management strategies such as incineration and biodegradation, chemical recycling offers the greatest value with potential to reduce the cost of PLA and increase market uptake . Previous examples of PLA recycling processes include hydrolysis, alcoholysis, hydrogenation and hydrosilylation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other waste management strategies such as incineration and biodegradation, chemical recycling offers the greatest value with potential to reduce the cost of PLA and increase market uptake . Previous examples of PLA recycling processes include hydrolysis, alcoholysis, hydrogenation and hydrosilylation …”
Section: Methodsmentioning
confidence: 99%
“…Commercially available metal salts and precursors have been shown to facilitate the transesterification of PLA to alkyl lactates, typically methyl lactate (Me‐La) . Sobota and co‐workers have also shown the use of metallic precursors at relatively high temperatures, demonstrating a range of alcohols for transesterification .…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29] A number of different PLA transesterification methods have been reported in the literature. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] DuPont possess a patent for PLA degradation in the presence of H 2 SO 4 , achieving high conversion (69-87%) to various lactate esters (R = Me, Et and n Bu) within 2 h between 150-190°C. 30 Coszach et al 17 demonstrated the hydrolysis of PLA to lactic acid, observing enhanced PLA dissolution and polymer separation with lactate esters as the solvent of choice.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches are not suitable for compositing because of the use of chemical compounds, which add to the environmental load. Enzymes [ 25 , 26 , 27 ] and metal compounds [ 28 ] have also been used as catalysts for PLA degradation. Some environmentally friendly materials such as clay can be used, but they increase the treatment time by several hours, necessitating larger plants for degradation.…”
Section: Introductionmentioning
confidence: 99%